Contribution of recreational fisheries to the diet of the opportunistic Kelp Gull - Marinao, Cristian Javier (2018)
We assessed Kelp Gull (Larus dominicanus) diet composition complementing conventional and stable isotope methods to determine the relevance of food derived from recreational fisheries. To achieve this goal, we quantified Kelp Gull diet composition breeding at the Bahía San Blas protected area, Argentina, between 2012 and 2014, assessing differences among four colonies, breeding stages and years. Diet analyses were based on pellets (n = 1054), chick stomach content samples (n = 351) and stable isotope analysis of adult and chick whole blood samples (n = 20 and 40, respectively). Kelp Gulls fed on at least 41 prey items, mainly fish complemented by marine invertebrates, Oat grain and insects. Stripped Weakfish (Cynoscion guatucupa), a demersal species, was in general the most frequent species among fish prey. Analyses of similarity indicated that diet composition based on pellet analysis was significantly different among the four colonies and, with a couple of exceptions, differed among breeding stages. Diet composition differed only between 2012 and 2013. Bayesian mixing model outputs confirmed demersal fish had in general the highest contribution to Kelp Gull diet. Stripped Weakfish is the most important target of recreational fisheries in the study area, and large quantities of waste resulting from the processing of this and other target fish is disposed mainly along the shore and in the Bahía San Blas refuse dump. The fact that it is a demersal species normally unavailable to surface feeding seabirds and the large size of Stripped Weakfish individuals found in diet samples (mean 41.5 ± 5.2 cm) strongly suggest that Kelp Gulls obtained this prey from the waste generated by the recreational fishery. Results show a strong association between the Kelp Gull and the recreational fishing activity that takes place in the Bahía San Blas protected area, likely resulting from the large amount of waste generated by the fishery.